1981
DOI: 10.1530/acta.0.0970166
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative differences in the isoelectrofocusing profile of biologically active lutropin in the blood of normally menstruating and post-menopausal women

Abstract: A single bolus of 100 \ g=m\ g of gonadoliberin (LRH) was administered intravenously to 8 post-menopausal and 9 normally menstruating women and blood was withdrawn before and 30, 60, 120 and 240 min after LRH stimulation. The plasma samples obtained at different time intervals from women showing a sufficiently high response to LRH (menopausal: 8, menstruating: 3) were combined and 2 ml samples of each pool were fractionated in triplicate by electrofocusing on sucrose density gradient. In addition, two plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Whether this observation has physiological significance or is due to the alterations in cytoarchitecture of cells in culture is presently unknown. Multiple species of secreted LH (Strollo et al 1981) and FSH ) have been separated from plasma and urine samples of women. Further, the isoelectric profile of LH in plasma appears to vary with the endocrine status of the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this observation has physiological significance or is due to the alterations in cytoarchitecture of cells in culture is presently unknown. Multiple species of secreted LH (Strollo et al 1981) and FSH ) have been separated from plasma and urine samples of women. Further, the isoelectric profile of LH in plasma appears to vary with the endocrine status of the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Due to variations in glycosylation, microheterogeneities of LH and hCG isoforms with varying bio-to immunoactivities have been detected by means of in vitro LH bioassays based on androgen production after short-term incubation of mouse and rat Leydig cells [1][2][3][4][5][6][7]. In addition, findings of immunoreactive but biologically inactive LH isoforms have led to the identification of an infertile patient with a defective LH3 gene due to a single amino acid substitution at codon 54 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The steroid environment can influence this heterogeneity, thereby controlling the type, as well as the amount, of gonadotrophin released by the pituitary (Bogdanove et al, 1975;Strallo et al, 1981;Wide, 1982). Several studies in the human have reported an increase in the biological activity of LH over the prepubertal period without similar changes in immunological LH activity (Neill et al, 1977;Lucky et al, 1980;Reiter et al, 1982).…”
Section: Introductionmentioning
confidence: 99%